Significance of Sahaja Yoga meditation in reducing academic stress - Jaysing Malhari Hotkar (Wolters Kluwer Medknow Publications, 2017)
Background of Study: The Indian school education system is textbook-oriented that focuses on rote memorization of lessons and demands long hours of systematic study every day. The elaborate study routines that are expected by high school students span from the morning to till late evening hours, leaving little time for socialization, recreation, play games and sports by full strength. Objective of Study: The present study was conducted with a view to see the effect of Sahaja Yoga meditation on stress among school children. Materials and Method: Non-equivalent control group design was used for this experiment. The participants were 8th grade students from a school located in Mumbai. The students were randomly assigned to control and experimental groups. Experimental group received the treatment of Sahaja Yoga meditation program for 6 weeks, whereas the control group did not receive any treatment. Both groups were free to do their daily routine activities. Stress was assessed using a questionnaire before and after 6 weeks of Sahaja Yoga meditation program. Statistical Analysis: Collected data were analyzed with the help of the standard statistical technique t-test to conclude the investigation. Results: The results of the study showed a significant difference in academic stress (p < 0.05) after 6 weeks of Sahaja Yoga meditation program. However, there was no significant improvement in academic stress (p > 0.05) in the control group. Conclusion: Sahaja Yoga meditation program is helpful to manage the academic stress of school girls.